2002
DOI: 10.1097/00126334-200211010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Strategies to Reduce Mother-to-Child HIV-1 Transmission in Argentina, 1993–2000

Abstract: This study evaluated the success of a national program for the prevention of mother-to-child transmission (MTCT) of HIV-1 in 874 mother-infant pairs from Buenos Aires and surroundings. This population was referred to the National Reference Center for AIDS for diagnosis of neonatal infection during 1993-2000. The data revealed an increase in the use of antiretroviral therapy during pregnancy from 3.2% in 1993-1994 to 73.1% in 1999-2000 and in the use of cesarean delivery (reaching 54.8% in 1999-2000). However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
5
0
3
Order By: Relevance
“…Two reports from Mexico City prior to the era of combination ART and other reports from Latin America found heterosexual transmission as the most frequent HIV-associated risk factor among pregnant women. [12][13][14][15] All women identified during prenatal care delivered by scheduled cesarean section, 53% in the absence of labor in contrast to 4% of women identified at the labor unit. Previous studies in Mexico have shown lower rates of cesarean section (25%) in women enrolled during pregnancy without specification of onset of labor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two reports from Mexico City prior to the era of combination ART and other reports from Latin America found heterosexual transmission as the most frequent HIV-associated risk factor among pregnant women. [12][13][14][15] All women identified during prenatal care delivered by scheduled cesarean section, 53% in the absence of labor in contrast to 4% of women identified at the labor unit. Previous studies in Mexico have shown lower rates of cesarean section (25%) in women enrolled during pregnancy without specification of onset of labor.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Studies in Latin America have shown lower rates of elective cesarean section but 1 study in Argentina showed an increase in the use of elective cesarean section from 19% to 54% between 1993 and 2000. [14][15][16] Recently, a National Institute of Child Health and Human Development (NICHD) Perinatal Study conducted in Latin America found a similarly high cesarean section rate in their Mexican site at 61% among HIV-infected women enrolled during prenatal care. 17 In addition, the same study found a similar rate of preterm delivery at 9% as in our current study.…”
Section: Discussionmentioning
confidence: 99%
“…10 Dentre os fatores associados à transmissão materno-infantil, destacam-se: a alta carga viral materna, a ruptura prolongada das membranas amnióticas, a presença de infecção sexualmente transmissível, o tipo de parto, a prematuridade e o uso de drogas. 4,8,15 Desde 1994, depois da divulgação do protocolo 076 do Aids Clinical Trial Group (PACTG 076), sabese que o uso da zidovudina (AZT) pela gestante infectada e pelo recém-nascido, durante as primeiras semanas de vida, pode reduzir em cerca de 70% o risco de a criança ser infectada, sendo considerado um dos principais avanços no conhecimento sobre a Aids. 5 Além disso, sabe-se, atualmente, que o uso de terapia anti-retroviral combinada, ou seja, a utilização simultânea de duas ou mais drogas anti-retrovirais, é capaz de reduzir significativamente a carga viral plasmática da mãe para níveis não detectáveis, reduzindo, assim, o risco de transmissão do HIV para o recém-nascido.…”
Section: Introductionunclassified
“…Transmission from mother to child is the main route of infection among children, accounting for over 90% of children in infections [9]. Risk factors for mother to child transmission include high maternal viral load [10-12, advanced maternal immune deficiency [13], prolonged rupture of membranes [14] and the presence of sexually transmitted infection, type of delivery, prematurity and drug use [15][16][17]. Risk factors related to transmission of HIV through breast milk have been less studied, but transmission by this route was associated with either viral load as subclinical mastitis [18].…”
Section: Hiv Vertical Transmissionmentioning
confidence: 99%